Actual problems about improvement car fleets to abroad through the Ukrainian networks - Hermaniuk, Yu. M. (Science and Transport Progress, 2011)
The article describes the basic problems of organization of international transit transportations. A statistical analysis of wagon delays at border stations has been done. Also some conclusions on the necessity of developing a mathematical model of pushing on the transit streams of wagons on the railway system in Ukraine have been done using the method of simulative modeling.